Upaya Guru PAI dalam Meningkatkan Kemampuan Baca Tulis Al-Qur'an Kelas VII di SMP Negeri 2 Cisitu Sumedang - R. Latifah Ahmad; Dinar Nur Inten; Ikin Asikin (UNISBA Press, 2023)
Abstract. Al-Qur'an is a source that is used as the basis of Islamic education. To be able to study and understand the contents of the Qur'an, a Muslim must have the ability to read the Qur'an first. Reading the Qur'an is a basic ability that must be possessed by every student. Teaching the Al-Quran is the treatise of Allah SWT and the mission of Islamic education that must be carried out by educators in educating their students. The purpose of this study was to find out the efforts made by Islamic Education teachers in improving the ability to read and write the Qur’an at Junior high school 2 Cisitu Sumedang. Based on the explanation above, the problems in this study are formulated as follows: (1) How is the reading and writing ability of the Al-Qur'an class VII students at Junior high school 2 Cisitu Sumedang? (2) What are the efforts taken by Islamic Education teachers in solving the obstacles to increasing the reading and writing ability of the Al-Qur'an for class VII students at Junior high school 2 Cisitu Sumedang? (3) What are the supporting and inhibiting factors for the Islamic Education teacher's efforts to improve the reading and writing ability of the Al-Qur'an class VII students at Junior high school 2 Cisitu Sumedang? This research uses a qualitative approach using the case study method. Then the data is analyzed and presented in a descriptive form. Data collection techniques used are observation, interviews and documentation. Abstrak. Al-Qur’an adalah sumber yang dijadikan landasan dalam pendidikan Agama Islam. Untuk dapat mempelajari dan memahami kandungan Al-Qur’an, seorang muslim harus memiliki kemampuan untuk membaca Al-Qur’an terlebih dahulu. Membaca Al-Qur’an adalah kemampuan dasar yang harus dimiliki oleh setiap siswa. Mengajarkan Al-Quran merupakan risalah Allah SWT dan misi pendidikan islam yang harus dilaksanakan oleh pendidik dalam mendidik anak didiknya. Tujuan dari penelitian ini adalah untuk mengetahui upaya yang dilakukan oleh guru PAI dalam meningkatan kemampuan baca tulis Al-Qur’an di SMP Negeri 2 Cisitu Sumedang. Berdasarkan penjelasan di atas, maka permasalahan dalam penelitian ini dirumusakan sebagai berikut: (1) Bagaimanakah kemampuan baca tulis Al-Qur’an siswa kelas VII di SMPN 2 Cisitu Sumedang? (2) Bagaimana upaya yang ditempuh guru PAI dalam memecahkan hambatan peningkatan kemampuan baca tulis Al-Qur’an siswa kelas VII di SMPN 2 Cisitu Sumedang? (3) Apa faktor pendukung dan penghambat upaya guru PAI dala meningkatkan kemampuan baca tulis Al-Qur’an siswa kelas VII di SMPN 2 Cisitu Sumedang?. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi kasus. Kemudian data tersebut dianalisis dan disajikan dalam bentuk deskriptif. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara dan dokumentasi.